Suppression of thromboxane A2 but not of systemic prostacyclin by controlled-release aspirin. - Clarke, R; Mayo, G; Price, P; FitzGerald, G (1991)
BACKGROUND: The antithrombotic efficacy of aspirin is attributed to its inhibition of the enzyme prostaglandin G/H synthase, which is necessary for the formation of thromboxane A2 in platelets. Thromboxane A2 is a potent vasoconstrictor and platelet agonist. However, the formation of prostacyclin by vascular endothelium also requires prostaglandin G/H synthase, and prostacyclin exerts opposite effects on platelet function and vascular tone. We wanted to see whether controlled-release aspirin would affect the formation of thromboxane A2 but not prostacyclin by reducing the aspirin concentration that reaches the posthepatic circulation. METHODS: A controlled-release formulation containing 75 mg of aspirin, designed to release 10 mg per hour, was developed to inhibit prostaglandin G/H synthase in platelets in the prehepatic circulation. The effects of the controlled-release preparation on plasma levels of aspirin and salicylate, serum levels of thromboxane B2, and urinary dinor metabolites of prostacyclin and thromboxane B2 (measured by gas chromatography-mass spectrometry) were compared with those of conventional immediate-release aspirin in normal volunteers. Prostacyclin release was stimulated by intravenous bradykinin. RESULTS: Steady-state inhibition of serum thromboxane B2 required two to four days and appeared slower with 75 mg of controlled-release than with the same amount of immediate-release aspirin. Maximal inhibition was achieved rapidly by adding a single loading dose of 162.5 mg of immediate-release aspirin to the regimen. Over a 28-day period, suppression of thromboxane A2 with this regimen was comparable to that with immediate-release aspirin taken either as 162.5 mg daily or as 325 mg on alternate days, despite the minimal systemic bioavailability of controlled-release aspirin. Bleeding time was prolonged to a similar degree with each of the three regimens. The five- to sixfold increase in the prostacyclin metabolite induced by bradykinin was depressed by pretreatment for four days with 75 mg of immediate-release aspirin, but not by 75 mg of controlled-release aspirin. CONCLUSIONS: Maximal inhibition of platelet thromboxane A2 production was sustained during long-term dosing with controlled-release aspirin, whereas basal prostacyclin biosynthesis fell only slightly and systemic synthesis of prostacyclin stimulated by bradykinin was preserved. Controlled-release aspirin may facilitate determination of the clinical importance of preserving prostacyclin during platelet inhibition in humans.